EFEKTIVITAS PROGRAM TERMINAL PARKIR ELEKTRONIK (TPE) DI DKI JAKARTA (STUDI KASUS JALAN H. AGUS SALIM ATAU JALAN SABANG JAKARTA PUSAT) - Pradipta, Rizky; Hariani, Dyah (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Electronic parking terminal (TPE) is a meter-based parking system that works electronically and is designed with a computerized system in real time. Electronic parking terminal (TPE) in Jakarta is present as a program and a short-term solution within the framework of the arrangement of roadside parking (on street parking). This study uses many theories from experts relevant to the program effectiveness, that are understanding of the program, socialization program, program's goals, real change, and monitoring and control systems that are educational. The research uses qualitative descriptive approach, data collection technique uses interviews, observation, and documentation. Informants in this study are Parking Unit Management (Unit Pengelola Perparkiran) Province of Jakarta, parking officers, and society. Electronic parking terminal (TPE) in H. Agus Salim road, Central Jakarta can be quite effective, although there are still obstacles such as lack of socialization directly to the public and the lack of public interest to read the leaflet supplied by Parking Unit Management (Unit Pengelola Perparkiran) Province of Jakarta. Supporting factor are the organizational structure, areas of synergy and cooperation, external parties, policies related to the implementation of the TPE, and financial resources. While the obstacles factors are the lack of workers to supervise and practicing supervision management. Recommended to Parking Unit Management (Unit Pengelola Perparkiran) Province of Jakarta to increase socialization to society, raising public awareness to use the card electronic money in the payment of parking, maintaining safety and comfort, making policy on the supervision and control, add personnel to supervise, maintain cooperation between the fields, improving management practices especially supervision.